Chemical probe mediated visualization of protein S-palmitoylation in patient tissue samples - Schek, Nancy; Lee, Jia-Ying; Burslem, George M.; Witze, Eric (Frontiers in Physiology, 2023)
While protein palmitoylation has been studied for decades, our understanding of its clinical importance is minimal compared to other post translational modifications. Since there are no antibodies to palmitoylated epitopes we are unable to correlate levels of protein palmitoylation in biopsied tissues at a meaningful resolution. The most common method for detecting palmitoylated proteins without metabolic labelling is through chemical labeling of palmitoylated cysteines with the acyl-biotinyl exchange (ABE) assay. We have adapted the ABE assay to detect protein palmitoylation in formalin fixed paraffin embedded (FFPE) tissue sections. The assay is sufficient to detect subcellular regions of cells with increased labeling which indicates areas enriched in palmitoylated proteins. To visualize specific palmitoylated proteins in both cultured cells and in FFPE preserved tissue arrays we have integrated the ABE assay with a proximity ligation assay (ABE-PLA). Our findings demonstrate for the first time that FFPE preserved tissues can be labelled with unique chemical probes to detect either areas enriched in palmitoylated proteins or the localization of specific palmitoylated proteins using our ABE-PLA methodology.